Stassis, Andreas - (:unkn) unknown (My University, 2026)
Andreas Stassis is an Assistant Professor at the Mechanical Engineering and Materials Science and Engineering Department. He received a BSc (Honours) in Production Engineering (1982) and a PhD in the field of Mechanical Vibrations (1986), at Leeds Polytechnic (UK). During 1986 he was the Production Manager of a Local Manufacturing Firm. From 1987 to 1989 he was a Lecturer in Mechanical Engineering at a Private University in Nicosia where he later became the Head of the Mechanical Engineering Department. From 1989 to 2010 he was a Lecturer in the Mechanical and Marine Engineering Department at the Higher Technical Institute, Nicosia. His research interests are mainly in improvements of vibrating structures, productivity improvements and elimination of waste in Manufacturing Industry.
Keywords: agric